Performance Evaluation through Value Added Ratios: A Case study of Ambuja Cement Ltd with Additive Method of Value Added - Chirodiya, Ashish Premjibhai (Celebes Scholar pg, 2024)
This paper is a case study of Ambuja Cement Ltd for the performance evaluation. Ambuja Cement Ltd is one of the leading Cement manufacturer company in India. This study is based on 5 years of period started from 2017-18 to 2021-22. To analyze its performance, Value Added Ratios (VARs) are used. Value Added Ratios (VARs) are very important in the analysis of Value related data. Total five important ratios are used and for statistical analysis Chi-Square test is used to know whether performance of the company is consistent or not. Chi-Square – goodness of fit test is used with an assumption that performance of the company is consistent if actual data “fits” expected data. Value Added (with the help of Additive method) and Value-Added Ratios (VARs) shows that Ambuja Cement Ltd is consistent in most of its financial activity and sound in the financial performance.